2016
DOI: 10.1177/0363546516667266
|View full text |Cite
|
Sign up to set email alerts
|

Functional Performance Among Active Female Soccer Players After Unilateral Primary Anterior Cruciate Ligament Reconstruction Compared With Knee-Healthy Controls

Abstract: Background: Good functional performance with limb symmetry is believed to be important to minimize the risk of injury after a return to pivoting and contact sports after anterior cruciate ligament reconstruction (ACLR). Purpose: This study aimed to investigate any side-to-side limb differences in functional performance and movement asymmetries in female soccer players with a primary unilateral anterior cruciate ligament (ACL)–reconstructed knee and to compare these players with knee-healthy controls from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 44 publications
(118 reference statements)
6
45
0
2
Order By: Relevance
“…Mientras que Waldén et al 10 y Guzzini et al 11 confirman una tasa de RPD del 100%, existen porcentajes más bajos tanto en el estudio de Sandon et al 12 como en el de Fältström et al 2 con un 54.1% y un 52% respectivamente. Las tasas de RPD extremidad reconstruida en comparación con la extremidad no afectada, difiriendo sólo mínimamente en algunas pruebas con los jugadores sanos 19 . Además, Thomson et al 18 apuntan que existe una descarga de peso relativamente grande de la extremidad operada a pesar de haberse completado el RPD.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Mientras que Waldén et al 10 y Guzzini et al 11 confirman una tasa de RPD del 100%, existen porcentajes más bajos tanto en el estudio de Sandon et al 12 como en el de Fältström et al 2 con un 54.1% y un 52% respectivamente. Las tasas de RPD extremidad reconstruida en comparación con la extremidad no afectada, difiriendo sólo mínimamente en algunas pruebas con los jugadores sanos 19 . Además, Thomson et al 18 apuntan que existe una descarga de peso relativamente grande de la extremidad operada a pesar de haberse completado el RPD.…”
Section: Resultsunclassified
“…A la hora del RPD tras la reconstrucción, no todos los participantes lo pueden hacer al mismo nivel previo a la lesión. En el estudio de Howard et al15 sólo el 75% vuelve a la misma categoría mientras que en otros cuatro estudios sí consiguen completar el RPD en el mismo nivel10,14,16,17 .En relación al rendimiento, sólo lo analizan tres estudios[17][18][19] . Se indica que no hay diferencias significativas entre el nivel anterior y posterior a la lesión17 , ni tampoco hubo deficiencias en la…”
unclassified
“…Many young athletes return to knee-strenuous sports after ACLR, often without recovering sufficient muscle function. 7 Many young female soccer players, with and without ACLR, have movement asymmetries and a high knee abduction moment, 12 which might predispose them to increased risk for primary 21 and secondary ACL injury. 23,31 Functional performance and individualized rehabilitation are important after ACLR.…”
Section: Discussionmentioning
confidence: 99%
“…The women in this study have been previously reported on in a larger cohort study examining women football players after ACL reconstruction and their uninjured peers [6]. Study methodology is presented here in brief as the methods are similar to the previous study [6]. All players received written and verbal information about the study, and gave written informed consent prior to testing.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria for this study were football players, between the ages of 16-25, with no history of ACL injury. The forty-six women included in this study were recruited as previously described [6], and selected from the larger female cohort because appropriately matched male football players were identified. The forty-six male football players were recruited from local football teams via word of mouth, coaches, and short presentations by the researchers to the team and matched to the women based on age, training frequency, and playing position ( Fig.…”
Section: Methodsmentioning
confidence: 99%